Penentuan Karakteristik Fisikokimia dan Fungsional Minuman Teh (Camellia sinensis L.) dalam Kemasan - Pratiwi, Yunanda Anggi Ilda; Rahmadi, Isnaini; Muzakki, Wafi Adizara; Wahyuningtyas, Amalia (Communication in Food Science and Technology, 2024)
Tea contains chemical compounds that are beneficial to the body, such as phenolic compounds. Packaged tea drinks are obtained from steeping tea with the addition of water, sugar, synthetic flavors, stabilizers, acidity regulators, and food additives that are tightly packaged. This research aims to evaluate the suitability of the quality of packaged tea drinks based on SNI requirements and determine physicochemical characteristics which include pH and total dissolved solids, while functional properties include total phenols and antioxidant activity. This research used a purposive sampling technique designed with a Completely Randomized Design with two duplicate replications. The results of the physicochemical and functional characteristic tests were analyzed using the ANOVA method and DMRT with α=5%. The results show that ready-to-drink tea products have a pH value between 5.4–6.79, total dissolved solids with a value of 6.5–8.2 °Brix, and antioxidant activity with a value of 56.83%–79.15%, where in terms of physicochemical content and functional properties, the five samples of packaged tea drinks can be said to be good. However, only 3 of the 5 samples had phenol content that was in accordance with that required by SNI 3413 of 2011.